An analysis of the distributional impact of excise duty in Uganda using a tax-benefit microsimulation model - Susan Namirembe Kavuma; Christine Byaruhanga; Nicholas Musoke; Patrick Loke; Michael Noble; Gemma Clare Wright (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
The distributional analysis of consumption taxes is useful for establishing the welfare impact of tax policy. This paper uses the UGAMOD microsimulation model to establish the tax incidence and welfare impact of excise duty in Uganda. The results reveal that households in the top deciles pay more in excise duty as a percentage of their consumption than households in the bottom deciles. Post-fiscal consumption is almost the same as pre-fiscal consumption for the first seven deciles, but there is a sharp reduction in post-fiscal consumption in the tenth decile. The paper also examines a policy reform in excise duty on mobile phone airtime, notes an annual increase in tax revenue of UGX 8,371 million, and does not observe an overall change in income inequality or poverty. It concludes that UGAMOD is a useful tool for tax policy makers to evaluate the impact of tax reforms on revenue collection and welfare.
Keywords: D31; E17; H20; H22; 330; excise duty; microsimulation; poverty; Uganda